Caracterização da estrutura de hábitat ao longo de um gradiente ambiental e análise de sua influência na distribuição das espécies ameaçadas de guigós (Callicebus spp.) do Nordeste brasileiro - Mendes, Raone Beltrão (2010)
Callicebus is one of the most widespread and diverse genera of Neotropical primates (Infraorder Platyrrhini). Two species in the Northeast of Brazil are threatened with extinction, due primarily to habitat loss and fragmentation. Conservation of these species is hampered by the lack of reliable information on their geographic distributions, and the condition of the ecosystems they inhabit. In order to understand the present-day distribution of the most endangered species (Callicebus barbarabrownae and Callicebus coimbrai), it is necessary to identify the determining factors, both biotic (e.g. intra- and interspecific interactions, population dynamics, resource availability) and abiotic (e.g. humidity, temperature, habitat structure). The objective of the present study was to comprehend the factors that influence the geographic distribution of C. barbarabrownae and C. coimbrai in the study area, through the evaluation of biotic (tree species) and abiotic (habitat structure) variables, in addition to the spatial distribution of the fragments. A total of 70 habitat fragments were surveyed in the lower Rio São Francisco basin in Sergipe, ranging from the coastal Atlantic Forest to the arboreal Caatinga. Callicebus was present at 16 sites, 13 of which were new localities for the genus. The habitat structure of nine fragments (Callicebus present or absent) was evaluated using a grouping analysis of biotic, abiotic and combined biotic/abiotic variables, revealing a distinct grouping among fragments from the Caatinga (94%, 56% and 73% similarity, respectively) and the Atlantic Forest (92%, 14% and 50% similarity, respectively). The fragments representing the Agreste (ecotone) grouped either with those of the Atlantic Forest or the Caatinga, reflecting the intermediate character of this system. The analysis of the spatial structure of the distribution of Callicebus revealed a positive correlation among the fragments representing the Atlantic Forest (Moran s I = 0.702 to 0.961) and Caatinga (I = -1.043 to -0.872), and a negative correlation between these two groups, with a clear lacuna of approximately 70 km in the distribution of the genus, coinciding with the Agreste. This reinforces the idea that the species C. barbarabrownae and C. coimbrai are distinct and endemic to the Caatinga and Atlantic Forest, respectively. These findings reinforce the need for the development of distinct conservation and management strategies for the different populations of these species, given that they face quite distinct ecological conditions in the wild.